The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.bpj.2011.11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 2 Reverses Tail-Independent Inactivation of Kinesin-1

Abstract: openAccessArticle: TruePage Range: 368a-368adoi: 10.1016/j.bpj.2011.11.2012Harvest Date: 2016-01-12 15:10:22issueName:cover date: 2012-01-31pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…The averages of velocities (Figure B) and run lengths (Figure C) of the small and large mitochondria in the cell body were independent of size. Importantly, the average velocity of ∼800 nm/second is typical of the unloaded velocity for both kinesin and dynein . Thus, in the cell body, the effect of drag appears negligible consistent with a previous lipid droplet study in drosophila embryos .…”
Section: Resultssupporting
confidence: 88%
“…The averages of velocities (Figure B) and run lengths (Figure C) of the small and large mitochondria in the cell body were independent of size. Importantly, the average velocity of ∼800 nm/second is typical of the unloaded velocity for both kinesin and dynein . Thus, in the cell body, the effect of drag appears negligible consistent with a previous lipid droplet study in drosophila embryos .…”
Section: Resultssupporting
confidence: 88%
“…It is also possible that the force‐based interaction between motors (not included in the theoretical model) could be altered by the nucleotide state of tubulin in microtubules. Lastly, although extensive in vitro studies suggest that this is unlikely (Block et al, ; Gelles et al, ; Xu et al, ), it is formally possible that polystyrene beads may alter the interactions between the motor and the microtubule in unexpected ways. Since it is challenging to completely rule out these potential concerns in biophysics‐based assays, we next turned to a biochemistry‐based assay.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Thus, there is significant interest in achieving a mechanistic understanding of their singlemolecule function, and in relating this to ensemble function involving multiple motors. [8][9][10][11][12][13] In our single-molecule studies of kinesin-1, we observed surprising heterogeneity of function: many motors moved relatively rapidly (~800 nm/s), but some moved significantly slower (eg,~200 nm/s). We initially ignored this slower population as "unhealthy," and focused on the faster population.…”
Section: Introductionmentioning
confidence: 84%
“…Purification of Drosophila full‐length kinesin is as explained in Reference . To ensure that the population of kinesins are chemically “identical”, we expressed the functional, truncated kinesin (K560) and K‐560gfp in E. coli and purified it as reported earlier . The procedure briefly is, E. coli Rosetta cells were transformed, and grown at 37°C from a single colony in 500 mL of terrific broth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation